Respuesta :

it will factor 2(x+3)(x-2)
so the answers are -3 and 2

Answer:

x = -3   x = 2

Step-by-step explanation:

[tex]2x^{2} + 2x - 12 = 0\\[/tex]

First divide every term by 2.

[tex]2x^{2} + 2x - 12 = 0\\[/tex]

/2       /2     /2     /2

It now simplifies to...

[tex]x^{2} + x - 6 = 0[/tex]

Now you have to find 2 values that multiply to -6 and add to 1.

These numbers are 3 and -2

(x + 3)(x - 2) = 0

Now make a T-chart or separate both terms and equal them to 0 and solve.

x + 3 = 0                     x - 2 = 0

x = -3                           x = 2

Plug both values in the original equation one at a time and check if the equation equals zero.

ACCESS MORE